HUBUNGAN PAPARAN PANAS DENGAN TEKANAN DARAH PADA PEKERJA PABRIK BAJA LEMBARAN PANAS - Lestari, Dinda Tri; Rahardjo, Mursid; Dewanti, Nikie Astorina Yunita (Fakultas Kesehatan Masyarakat, 2018)
Heat stress exposure is often found in the industrial environment that exposed workers at risk for increasing blood pressure. This study investigated the associations of heat stress exposure with blood pressure on steel industry workers. This research is an observational study with cross sectional design. The study population was 27 workers in production area and 13 workers in control room selected by probability sampling method. The data were analyzed by using Rank Spearman Correlation with 95% confidence level. Workers in production area had significantly higher levels of systolic blood pressure (SBP) (137.52±14.98 mmHg) and diastolic blood pressure (DBP) (86.41±9.64 mmHg) than workers in control room (SBP : 119.15±10.92 mmHg, DBP : 77.62±5.17 mmHg). The results of this study show that heat stress were positively correlated with systolic (p=0,000) and diastolic (p=0,001). In conclusion, exposure to heat was a major risk factor for hypertension. Exposure to heat can elevate blood pressure. Therefore, workshops with high temperature must do their best to lower environment temperature in order to control blood pressure.